La démarche d'investigation depuis la théorie anthropologique du didactique : les parcours d'étude et de recherche - Floriane Wozniak (Nantes Université, 2015)
We consider that the inquiry-based method is a praxeology for answering a question. The didactic process named the dialectic of media and milieus provides the materials for producing an answer. The Herbartian schema describes the pedagogy of inquiry applied to a study and research path. We suggest that the Herbartian schema could be an epistemic model for the inquiry-based method. We show how this model can provide some conditions concerning mesogenesis, chronogenesis and topogenesis for a real use of inquiry-based method.